Chromosome analysis in saccodon wagneri (Characiformes) and insights into the karyotype evolution of parodontidae - Nirchio, Mauro; Masache, Maria Cecilia; Paim, Fabilene Gomes [UNESP]; Cioffi, Marcelo de Bello; Filho, Orlando Moreira; Barriga, Ramiro; Oliveira, Claudio [UNESP]; Rossi, Anna Rita (FapUNIFESP (SciELO), 2021)
Parodontidae is a relatively small group of Neotropical characiform fishes consisting of three genera (Apareiodon, Parodon, and Saccodon) with 32 valid species. A vast cytogenetic literature is available on Apareiodon and Parodon, but to date, there is no cytogenetic data about Saccodon, a genus that contains only three species with a trans-Andean distribution. In the present study the karyotype of S. wagneri was described, based on both conventional (Giemsa staining, Ag-NOR, C-bands) and molecular (repetitive DNA mapping by fluorescent in situ hybridization) methods. A diploid chromosome number of 2n = 54 was observed in both sexes, and the presence of heteromorphic sex chromosomes of the ZZ/ ZW type was detected. The W chromosome has a terminal heterochromatin band that occupies approximately half of the long arm, being this band approximately half the size of the Z chromosome. The FISH assay showed a synteny of the 18S-rDNA and 5S-rDNA genes in the chromosome pair 14, and the absence of interstitial telomeric sites. Our data reinforce the hypothesis of a conservative karyotype structure in Parodontidae and suggest an ancient origin of the sex chromosomes in the fishes of this family.
Keywords: Ag-NOR; Cytogenetics; FISH; Heterochromatin; ZW sex chromosomes